2022
DOI: 10.3343/alm.2022.42.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic Syndromes with Bone Marrow Fibrosis: An Update

Abstract: Myelodysplastic syndrome (MDS) is a diverse hematological malignancy with a wide spectrum of presentations and implications. Treatment strategies for patients with MDS heavily rely on prognostic scoring systems, such as the revised international prognostic scoring system (IPSS-R). Bone marrow fibrosis (BMF) has been identified as an independent risk factor for poor survival in patients with MDS, irrespective of the IPSS-R risk category. However, BMF is not widely included in scoring systems and is not always c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Most previous studies have found that patients with moderate to severe reticulin fibrosis (MF2-3) often had a poorer overall survival compared with patients with MF0-1. So only MF2-3 was considered as MDS-F in studies [ 8 , 15 , 17 , 18 ]. More recently, Melody et al [ 19 ] reported that only MF3 affected survival, when patients with MF3 were compared with those with MF0-2 fibrosis, based on an MDS database of 2624 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have found that patients with moderate to severe reticulin fibrosis (MF2-3) often had a poorer overall survival compared with patients with MF0-1. So only MF2-3 was considered as MDS-F in studies [ 8 , 15 , 17 , 18 ]. More recently, Melody et al [ 19 ] reported that only MF3 affected survival, when patients with MF3 were compared with those with MF0-2 fibrosis, based on an MDS database of 2624 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow fibrosis was seen in a variety of malignancies (e.g., multiple myeloma and myelodysplastic syndrome) and non‐malignancies (e.g., chronic autoimmune diseases, infections, and exposure to radiation or toxins). [ 31 , 32 ] It was likely that both malignant and non‐malignant diseases activate fibrosis‐driving cells by common downstream mechanisms. [ 33 ] Dry tap refers failure to obtain bone marrow on attempted marrow aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of BM biopsy sections helps with the assessment of stromal fibers (collagen types I/III, reticulin) representing marrow fibrosis [ 35 ]. About 10–20% of MDS patients show marrow fibrosis at presentation [ 36 , 37 , 38 ].…”
Section: Mds Prognostic Scoring Systemsmentioning
confidence: 99%